On the volatility of the yield curve of the Colombian public debt market (2018)
This paper estimates the volatility of the Temporary Structure of Interest Rates (ETTI) of the Colombian public debt market and explains its relationship with macroeconomics fundamentals. Starting from the parametric model proposed by Nelson and Siegel (1987), the ETTI is estimated in order to capture the conditional volatility component with the Autoregressive Conditional Heteroskedasticity models (ARCH). Subsequently the relationship with the macroeconomic variables such as the gross domestic product ( y ), the general price level ( ? ), the monetary policy interest rate ( i ) and the risk country ( r ) is evaluated through impulse-response function of the Structural Vector Autoregressive models (SVAR) and the Granger causality tests. The results show that the volatility of the ETTI of the Colombian public debt market has asymmetric effects and there are causal relationships in both directions with some of the macroeconomic variables. However, when there are shocks among them, there are only significant unidirectional responses from macroeconomics to ETTI volatility and not in the opposite direction.